2020
DOI: 10.1016/j.celrep.2020.107995
|View full text |Cite|
|
Sign up to set email alerts
|

A Switch in p53 Dynamics Marks Cells That Escape from DSB-Induced Cell Cycle Arrest

Abstract: SUMMARY Cellular responses to stimuli can evolve over time, resulting in distinct early and late phases in response to a single signal. DNA damage induces a complex response that is largely orchestrated by the transcription factor p53, whose dynamics influence whether a damaged cell will arrest and repair the damage or will initiate cell death. How p53 responses and cellular outcomes evolve in the presence of continuous DNA damage remains unknown. Here, we have found that a subset of cells switches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 70 publications
1
26
0
Order By: Relevance
“…The cells with sustained p53 signaling showed chromosomal damage. The authors found that late phase p53 levels were reduced in irradiated PIDD1-deficient cells and in cells following caspase-2 inhibition 79 . Overall, their data suggest that PIDD1 and caspase-2 are required for cells that evade DNA damage-induced cell cycle arrest to switch from pulsating to sustained p53 signaling.…”
Section: Caspase-2 Stabilizes P53 Following Dna Damagementioning
confidence: 97%
See 2 more Smart Citations
“…The cells with sustained p53 signaling showed chromosomal damage. The authors found that late phase p53 levels were reduced in irradiated PIDD1-deficient cells and in cells following caspase-2 inhibition 79 . Overall, their data suggest that PIDD1 and caspase-2 are required for cells that evade DNA damage-induced cell cycle arrest to switch from pulsating to sustained p53 signaling.…”
Section: Caspase-2 Stabilizes P53 Following Dna Damagementioning
confidence: 97%
“…On the other hand, in response to UV-induced DNA damage that activates ATR, p53 is expressed as a broad pulse 78 . A study published in 2020 suggests that several days after ionizing radiation-induced DNA damage, some cells switch from oscillating to sustained p53 dynamics 79 . Using a Venus fluorescent reporter to monitor p53 levels in single cells, the authors found that following 10 Gy irradiation, 15–20% of cells exhibit stably increased p53 levels 79 .…”
Section: Caspase-2 Stabilizes P53 Following Dna Damagementioning
confidence: 99%
See 1 more Smart Citation
“…The parameter values we used are shown in Table S1. The justification for these values is as follows: α, β, γ : taken from Tsabar et al (2020); σ : taken from Mönke et al (2017), rescaled to agree with Tsabar et al (2020); κ: taken from Monke et al (2017); the parameters σ, ϵ, ϕ and δ form a group, all affecting Mdm2 dynamics. As a reality check, we verified that the chosen set of parameters produced oscillations in p53 protein levels with the characteristic period of 5-6 hours Lahav et al (2004), as well as oscillations in MDM2 transcript and Mdm2 protein levels that are consistent with experimental observations (Hanson et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…after cytokinesis failure [57], placing caspase-2 upstream of p53. Alternatively, PIDDosome-activated caspase-2 has been proposed to act as a fail-safe mechanism by initiating a stable p53 response in cells that escape cell cycle arrest following DNA damage [137]. Here, caspase-2 may act as an important safeguard of genome integrity downstream of p53.…”
Section: Mitotic Catastrophe Caspase-2 and The Piddosomementioning
confidence: 99%